The Appointed Head Master’s Perception about the Inclusive Education Policy in Ambon City - Thomas A.H Sulistyo; Budiyanto Budiyanto (Department of Special Education, 2017)
The government’s policy on inclusive education is regulated through the Regulation of the National Education Minister of the Republic of Indonesia, number 70 year 2009, which becomes the formal rule covering the implementation of inclusive education in Indonesia. In Ambon city, the information transmission process on inclusive education policy has been implemented by the education office of Ambon city through a series of socialization activities both internally and externally. However, this issue is still controversy among schools between agree/pro and receive/refuse about the model of inclusive education. The situation indicates that the implementation of policies issued by the central government and local governments have not been absorbed by stakeholder in the bottom level. Based on the above problems, this study was needed more deeply for the school principal’s perception about the inclusive education policy in Ambon City. The purpose of this research was to explore various information related to school perceptions of inclusive education policy. This research used qualitative approach by conducting with in-depth-interviews and analyzing by using Flow Model of Analysis. Activities in the analysis included data reduction, data presentation as well as interpretation and conclusion. The results of the 13 principals implementing education have different perceptions about inclusive education. From 12 aspects of inclusive education strategy, there were 2 schools that can understand about the policy of inclusive education. Otherwise, 11 schools did not understand. The conclusions of this research was the perceptions of inclusive education policy from 13 principals implementating the inclusive education have not understood the inclusive education deeply.Kebijakan pemerintah tentang pendidikan inklusi diatur melalui Peraturan Menteri Pendidikan Nasional Republik Indonesia, nomor 70 tahun 2009, yang menjadi peraturan formal yang mencakup pelaksanaan pendidikan inklusif di Indonesia. Di kota Ambon, proses transmisi informasi pada kebijakan pendidikan inklusif telah dilaksanakan oleh dinas pendidikan kota Ambon melalui serangkaian kegiatan sosialisasi baik secara internal maupun eksternal. Namun, isu ini masih kontroversi di kalangan sekolah antara yang menerima dan menolak model pendidikan inklusif. Situasi tersebut mengindikasikan bahwa pelaksanaan kebijakan yang dikeluarkan oleh pemerintah pusat dan pemerintah daerah belum diserap oleh pemangku kepentingan di tingkat bawah. Berdasarkan permasalahan di atas, penelitian ini sangat dibutuhkan untuk mengetahui persepsi kepala sekolah tentang kebijakan pendidikan inklusif di Kota Ambon. Tujuan dari penelitian ini adalah untuk menggali berbagai informasi yang berkaitan dengan persepsi sekolah tentang kebijakan pendidikan inklusif. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan wawancara mendalam dan analisis dengan menggunakan Flow Model of Analysis. Kegiatan dalam analisis meliputi reduksi data, penyajian data serta interpretasi dan kesimpulan. Hasil dari 13 prinsipal pelaksana pendidikan memiliki persepsi yang berbeda tentang pendidikan inklusi. Dari 12 aspek strategi pendidikan inklusif, ada 2 kepala sekolah yang dapat memahami tentang kebijakan pendidikan inklusi. Sedangkan 11 kepala sekolah tidak mengerti. Kesimpulan dari penelitian ini adalah persepsi kebijakan pendidikan inklusif dari 13 kepala sekolah yang menerapkan pendidikan inklusi belum memahami pendidikan inklusi secara mendalam.